PENDIDIKAN KARAKTER PADA FILM MOMOTAROU: UMI NO SHINPEI (1945) - Gede Satya Hermawan (Universitas Pendidikan Ganesha, 2015)
ABSTRACT Momotaro: Umi no Shinpei must be identified as Japanese propaganda movie for world war 2 in 1945. All research always analysis on Japanese propaganda in Asia, particularly southeast asia. Through this research, the movie will be rechanged all about point of view about propaganda movie, which is the movie is a movie that is loaded with character education, such as cooperation, courage, responsibility, hard work, and creative. This study uses a semiotic Roland Barthes, Myth scheme. Taking the visual images that appear in the film as the data.Keyword: semiotic, character education,movie, momotarou: umi no shinpei